Changes in nucleosome occupancy occur in a chromosome specific manner - Sexton, Brittany S. (Elsevier, 2014)
In the eukaryotic nucleus, DNA is packaged into chromatin. The fundamental subunit of chromatin is the nucleosome, DNA is wrapped 1.6 times around a histone octamer core. Nuclear processes in eukaryotes are impacted by whether regulatory DNA is occupied by nucleosomes. We used microarrays to measure nucleosome occupancy in human cells post-Kaposi's sarcoma-associated herpesvirus (KSHV) reactivation at hundreds of immunity-related loci. The detailed analysis of these technologies can be found in recent publications from our lab [1,3]. We found that nucleosome redistributions displayed chromosome specific nucleosome occupancy. This resource can be used to map nucleosome distributions in a variety of biological contexts.